Wavy Leading Edge (WLE) Influence on a Rectangular Wing Using an Unsteady Analysis Approach - Iis Rohmawati; Hiroshi Arai; Ika Nurjannah (Mechanical Engineering Department - Institut Teknologi Adhi Tama Surabaya, 2023)
A rectangular wing with Wavy Leading Edge (WLE) effect was investigated experimentally and numerically. This research was carried out with the NACA 0018 profile. The morphology of humpback whale flippers, which are blunt and rounded in a specific pattern, inspired the design of the WLE. The rectangular wing was explored in pitching motion with a reduced frequency of k = 0.25 and varied aspect ratios. Multiple aspect ratios (AR) of the rectangular wing have been evaluated to determine the best wing aspect ratio, notably 3.9, 5.1, and 7.9. Only at AR 3.9 and 5.1 does the WLE perform efficiently in both upstroke and downstroke motion. WLE has a sinusoidal function shape. The improvement of lift force was stronger during upstroke motion than during downstroke motion. The stall is minimized during the pitching motion of the WLE wing, according to the numerical simulation. This result could be applied to fin stabilizers or wind turbines.